Innovative business models in online retailing - DENG, Qiyuan (Institutional Knowledge at Singapore Management University, 2020)
Internet has opened the door for e-commerce and created a business avenue, online retailing. E-commerce presently shapes the manner in which consumers shop for products. The online retailing markets have grown by 56% during the past five years, while traditional retailing markets are only grown by 2% during the same time. The noticeable growth of online retailing creates numerous opportunities as well as challenges for the context of operations management. Extensive literature in this domain focus on the conventional inventory management and pricing problems as in traditional retailing. However, the rapid development of information technology threatens the established business models and creates opportunities for new business models. Companies may find it increasingly difficult to make strategic decisions, such as how to deal with the challenge associated with online retailing and how to adapt to the new retailing environment. This thesis aims to investigate innovative business models involved in online retailing, to capture trendy phenomena that are under-studied, and provide managerial insights. The first chapter focuses on dealing with the logistics challenge caused by the booming e-commerce activities. An urban consolidation center (UCC) or a peer-to-peer platform may alleviate the economic, social and environmental pressure on well-being. We compare the performance of these two business models to guide a consolidator to make efficient operational decisions. The second chapter focuses on the channel management decisions of a retailer who operates an offline (brick-and-mortar) channel and an online channel. The two channels are either operated separately or integrated. We explore how the retailer can profitably integrate her offline and online channels, from a perspective of product descriptions and consumer reviews. The last chapter focuses on a seller's decisions in the process of entering the online market through online marketplaces. In addition to pure-play marketplaces, some marketplaces also sell their own products directly competing with sellers, which creates a new form of channel conflict. We analyze the optimal decisions for both the seller and the marketplaces to characterize the system equilibrium.